PENGELOLAAN PELAYANAN BIMBINGAN DAN KONSELING STUDI SITUS SMK SAKTI GEMOLONG - SUSILAWATI, MILAD KHOMSA (2011)
The objective of this research is to know how is the management of guidance and counseling service in SMK Sakti Gemolong. It takes two subfocuses, namely how is the characteristics of the structure and the organizational function of guidance and counseling service and also how is the characteristics of client counselor interaction of the guidance and counseling service in SMK Sakti Gemolong. This is a qualitative research which a descriptive approach. It takes some informants or sources who directly involved to the guidance and counseling service, such as the headmaster, the vice-headmaster of students affairs, the guidance and counseling coordinator, counselors, homeroom teachers, the teachers, the staff of administration, and also the students. In collecting the data, the researcher uses the method, namely observation, documentation, and deep interview. The characteristics of the structure and the organizational function of guidance and counseling service in SMK Sakti Gemolong show that the structure involves the roles of some school personnels, such as the headmaster, the vice- headmaster of students affairs, the guidance and counseling coordinator, counselors, homeroom teachers, the teachers, the staff of administration. All of them give the service as well as possible to all students. These guidance personnels have good function and role. They do not neglect the form of cooperation or collaboration to each personnel. The headmaster has responsibility to all activities of guidance and counseling service, then he delegates this to the vice-headmaster of students affairs, finally to the counselor coordinator. Then the counselors focus on guiding both individual and also group of students. The counselors collaborate with the homeroom teachers, the homeroom teachers focus on giving the base of guidance which is done classically, do the service of orientation, information, group guidance, and also applied instrumentation. The teachers of subject matter have the role to help the homeroom teachers and the counselors as the form of consultation in the guidance and counseling service to the students. The collaboration has given the colour and tone in creating a good and ideal condition at school. It can prevent the violation to the school's rules. The characteristics of client counselor interaction in guiding and counseling service in SMK Sakti Gemolong has run well and well organized, showed from the fields and kinds of services given to the students. All the services based on the students' needs. The effect is that t teaching learning process can be done well as the school planning. Both characteristics are able to collaborate harmoniously although actually an ideally that the guidance and counseling service must be done by a good counselor; who has competence and qualification; who has enough time to guide and give the service to the students, not personnel who has double role at school.